Association between dietary fiber intake and cancer cachexia: mediation by inflammatory biomarkers - Guo, Yan; Zhang, Caiyan; Wang, Haiyue; Xue, Hongmei; Xie, Ying; Du, Hongzhen; Li, Zengning (Frontiers in Nutrition, 2026)
BackgroundCancer cachexia (CC) is a major cause of death in cancer patients, with chronic inflammation being a key driver. Dietary fiber, a nutrient with strong anti-inflammatory potential, is closely linked to mortality risk in cancer patients. However, the association between dietary fiber intake and cachexia risk remains unclear.MethodThis study collected dietary and clinical data from cancer patients enrolled in the “Investigation for Current States of Dietary Intake and Its Influencing Factors in Patients with Common Cancers” (DIIFC). First, we analyzed the association between dietary fiber intake and cancer cachexia using restricted cubic splines (RCSs). Next, we used multivariable logistic regression models to analyze the relationships between dietary fiber intake, inflammatory markers, and cancer cachexia. Finally, we performed mediation analysis to explore whether inflammation mediates the effect of dietary fiber intake on cancer cachexia.ResultsOf the 720 participants, 198 were diagnosed with cancer cachexia. RCSs revealed a nonlinear inverse correlation between dietary fiber intake and the risk of cancer cachexia (p < 0.001). Logistic regression analysis showed that greater dietary fiber intake was associated with a lower risk of cachexia (OR = 0.92, 95% CI: 0.87–0.98, p = 0.007). Higher levels of inflammatory markers (WBC, NEU, and NLR) were associated with a greater risk of cachexia (p < 0.05). Mediation analysis indicated that WBC, NEU, and NLR significantly mediated the relationship between dietary fiber and cachexia, accounting for 5.67%, 7.62%, and 7.78%, respectively (p < 0.05).ConclusionIncreased dietary fiber intake may exert a protective effect against cancer cachexia, partially mediated through inflammatory pathways. Further exploration of specific fiber subtypes and additional mechanisms is warranted.